Análise das práticas da gestão do processo de desenvolvimento de produtos em empresas de revestimento cerâmico do pólo de Santa Gertrudes estado de São Paulo - Costa, Marcela Avelina Bataghin (Universidade Federal de São Carlos, 2010)
Brazil occupies an outstanding position in the ceramic tile industry worldwide. In 2009 became the second largest consumer market (534.7 million sq), the fifth largest exporter (81 million sq) occupying the second position in the global ranking of producers. The Pole of Santa Gertrudes is responsible for 50% of national production and 15% of total Brazilian exports of ceramic tile. But exports are growing at the Pole a lower rate than the state average. This is due in part to deficiencies in the capacity of the Product Development Process (PDP) by business the Pole, including the management of this process. Product innovations depend on technology suppliers of inputs and equipment which are usually multinational companies. This Master Thesis aims to describe and analyze the management of the process of product development in a representative sample of companies in the ceramic coating Polo Santa Gertrudes-SP, because of their economic importance, focusing on the identification of problems of their management the practices adopted in this process and propose improvements to the performance of the PDP, addressing the needs of current and future capacity of these companies. Was carried out a survey research through visits and face to face interviews in 20 companies of different sizes, located at the Pole ceramic Santa Gertrudes, São Paulo. The Pole has a total of 36 industrial enterprises, therefore the sample represents 55.6% of the population under study. The data are analyzed in order to characterize the companies, test possible correlations between study variables and group companies with similar characteristics into groups (clusters). A correlation analysis showed the dependence between some variables. The cluster analysis generated two clusters, differentiated mainly by the existence of formalized procedures that define the activities of PDP and the realization of export. The cluster I is composed of 14 medium and large and the cluster II by six midsize businesses. The companies in cluster I are characterized by being predominantly family management, the lack of separate design teams, no formal steps that define the activities of PDP and for failure to export their products, while businesses in the cluster II are characterized by a tendency the professionalization of its management, the existence of project teams, formalization of the activities of PDP and even incipient export their products. It was observed that is not common in both clusters the use of tools to support the management of the PDP. In general it is concluded that although the ceramics manufacturers that dictate the pace of production of its suppliers are the suppliers, particularly Colorificio, leading most of the activities of new product development, showing that there is still a dependency in relation to those suppliers, which are usually subsidiaries of multinationals.
Keywords: Desenvolvimento de produtos; Revestimento cerâmico; Santa Gertrudes (SP) - pólos; Gestão de processo de desenvolvimento de produtos; ENGENHARIAS::ENGENHARIA DE PRODUCAO